Role of genetics in the development of cardiac allograft vasculopathy - Mayerová, Lucie; Chaloupka, Anna; Wohlfahrt, Peter; Hubáček, Jaroslav; Bedáňová, Helena; Chen, Zhi; Kautzner, Josef; Melenovský, Vojtěch; Málek, Ivan; Tomášek, Aleš; Ozábalová, Eva; Krejčí, Jan; et al. (Bratislavské lekárske listy, 2023)
BACKGROUND: The association between genetic polymorphisms and early cardiac allograft vasculopathy (CAV) development is relatively unexplored. Identifi cation of genes involved in the CAV process may offer new insights into pathophysiology and lead to a wider range of therapeutic options. METHODS: This prospective study of 109 patients investigated 44 single nucleotide polymorphisms (SNPs) within the susceptibility loci potentially related to coronary artery disease, carotid artery intima-media thickness (cIMT), and in nitric oxide synthase gene. Genotyping was done by the Fluidigm SNP Type assays and Fluidigm 48.48 Dynamic Array IFC. The intima thickness progression (IT) was evaluated by coronary optical coherence tomography (OCT) performed 1 month and 12 months after heart transplantation (HTx). RESULTS: During the fi rst post-HTx year, the mean intima thickness (IT) increased by 24.0 ± 34.2 μm (p < 0.001) and lumen area decreased by ‒0.9 ± 1.8 mm2 (p < 0.001). The rs1570360 (A/G) SNP of the vascular endothelial growth factor A (VEGFA) gene showed the strongest association with intima thickness progression, even in the presence of the traditional CAV risk factors. SNPs previously related to carotid artery intima-media thickness rs11785239 (PRAG1), rs6584389 (PAX2), rs13225723 (LINC02577) and rs17477177 (CCDC71L), were among the fi ve most signifi cantly associated with IT progression but lost their signifi cance once traditional CAV risk factors had been added. CONCLUSION: Results of this study suggest that genetic variability may play an important role in CAV development. The vascular endothelial growth factor A gene SNP rs1570360 showed the strongest association with intima thickness (IT) progression measured by OCT, even in the presence of the traditional CAV risk factors (Tab. 3, Fig. 3, Ref. 36).